2014
DOI: 10.1590/s0100-67622014000600012
|View full text |Cite
|
Sign up to set email alerts
|

Banco de sementes como indicador de restauração em sistemas agroflorestais multiestraficados no sudoeste de Matto Grosso do Sul, Brasil

Abstract: RESUMO -Este estudo teve por objetivo avaliar a composição do banco de sementes como indicador de restauração em quatro módulos de sistemas agroflorestais multiestratificados, com diferentes idades e em remanescente florestal nativo no Município de Amambai, região Sudoeste do Estado de Mato Grosso do Sul. As coletas de solo foram realizadas em dezembro de 2012 e consistiram em 15 amostras de 20 cm x 20 cm, a 5 cm de profundidade, distribuídas ao acaso, em cada módulo do Sistema Agroflorestal e testemunha (mata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
(9 reference statements)
0
10
0
6
Order By: Relevance
“…Recent studies have shown agroforests increase the occurrence of native tree species and promote forest succession (Leite, 2014;Moressi et al, 2014), with characteristics similar to secondary forests. The role of AFS in maintaining and improving soil fertility, especially through the use of high biomass-producing species in nutrientdeficient soils, has also been documented by Vieira and colleagues (2009).…”
Section: Potential Benefits Of Agroforestry Systems For Restoration Imentioning
confidence: 99%
“…Recent studies have shown agroforests increase the occurrence of native tree species and promote forest succession (Leite, 2014;Moressi et al, 2014), with characteristics similar to secondary forests. The role of AFS in maintaining and improving soil fertility, especially through the use of high biomass-producing species in nutrientdeficient soils, has also been documented by Vieira and colleagues (2009).…”
Section: Potential Benefits Of Agroforestry Systems For Restoration Imentioning
confidence: 99%
“…Many studies evaluating seed banks in agroforestry systems were conducted as for vegetation regeneration and conservation purposes (Kozlowski, 2002;Diemont et al, 2006;Loha et al, 2008;Costa and Mitja, 2009;Moreira et al, 2011;Moressi et al, 2014). Moreover, fewer studies gave more emphasis to the productive aspects of agroforestry systems and the potential risks of the negative interference of weeds on crops (Akobundu et al, 1999;Ekeleme et al, 2003;López-Pintor et al, 2003;Ekeleme et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A regeneração natural é caracterizada pelo processo de estabelecimento e desenvolvimento do estrato inferior da floresta e suas relações com os processos bióticos e abióticos (Moressi et al, 2014;Alves et al, 2018). O sucesso do processo tanto quantitativamente como qualitativamente concebe a formação e preservação da floresta.…”
Section: Naunclassified